(3eMGSf GdeLGdS hLdhI GdYQGFSs - (3CMeO Hf eMeO Hf ehSi GdUfgGLj GdCfOdSj GdeQj, CHh GdYHGS , GHf GdnYQja,J (B536 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf s
(3de jfSH ai GdeNWhWI dPdc GdeDda hEfeG fSHg HQcdeGfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B164s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B232 s
Keywords: (3GdJGQjNs